Layered regulation of a pathway capable of altering quinolone production in Pseudomonas aeruginosa - Tipton, Kyle A. (East Carolina University, 2014)
Pseudomonas aeruginosa is a gram negative opportunistic pathogen which commonly infects hospitalized patients and those afflicted with cystic fibrosis. P. aeruginosa communicates intercellularly via a system of small diffusible molecules in the process of cell-to-cell signaling. The Pseudomonas quinolone signal (PQS) is one of these molecules and its synthesis is required for production of virulence factors such as pyocyanin. PQS is synthesized by the gene products of pqsABCD and pqsH, and it is a cofactor for the transcriptional regulator PqsR which then positively regulates the pqsABCDE operon. Many gene deletions have been identified that eliminate or suppress PQS production including biosynthetic and regulatory protein encoding genes. We have identified a gene which encodes an RpiR-type transcriptional regulator (PA5506; now designated qapR for quinolone alteration pathway regulator) that modulates PQS production through an unknown mechanism. A qapR deletion mutant was constructed in strain PAO1 and the phenotype of this mutant was characterized. The [delta]qapR mutant produced less PQS and pyocyanin than the wild type strain PAO1. We found that transcription from the pqsA promoter is reduced in the [delta]qapR mutant compared to wild type strain PAO1 and this reduction is due to decreased PQS concentration. Expression of PqsABCD in the[delta]qapR mutant was able to complement PQS and pyocyanin production which indicates that PQS precursor pools are unaffected by qapR mutation. Using gel-shift assays we showed that qapR encodes a transcriptional regulator capable of binding to the qapR operon (containing genes qapR, PA5507, PA5508, and PA5509) promoter. Quantitative real-time PCR showed a large increase in transcription of genes PA5507, PA5508, and PA5509 when comparing the qapR mutant to the wild type. All three of these genes are required to reduce PQS concentration when transcriptional repression of the operon is alleviated. Further investigation of the qapR operon lead us to construct a point mutant that introduced a premature stop codon in the qapR open reading frame. This mutation led to derepression of the qapR operon but did not affect PQS concentration. We found expression of gene PA5507 restored the low PQS phenotype to the qapR-C90G point mutant. Reporter fusions translationally linked to PA5507 allowed us to show that translation of this gene is coupled to that of the upstream regulator qapR. This second level of regulation allows P. aeruginosa to have intricate control over the qapR operon which can reduce PQS concentration.
Keywords: Microbiology; Aeruginosa; PQS; Pseudomonas; Cystic Fibrosis; Virulence Factors; Bacterial Proteins--metabolism; Pseudomonas aeruginosa--metabolism; Quinolones--metabolism